2012
DOI: 10.4236/aim.2012.24079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of <i>Listeria monocytogenes</i> Based on the PFGE and RAPD in Korea

Abstract: This study was performed to characterize 35 L. monocytogenes isolates from animals, foods, environmental samples collected between 1997 and 2007 with no apparent epidemiological relations, and five reference isolates using serotypic, genotypic and molecular typing methods to understand the pattern of strain distribution in Korea. For this study, we used serotyping and detected 6 different virulence-associated genes (inlA, inlB, plcA, plcB, hlyA, and actA) and 16s rRNA using multiplex-PCR. We also compared RAPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Listeriosis caused by Listeria monocytogenes is a bacterial infection with a high case-fatality rate (CFR) of approximately 20% to 30%; listeriosis occurs mainly in the elderly, neonates, immunocompromised patients, and pregnant women via central nervous system (CNS) infection and bloodstream infection (BSI) [ 1 2 3 4 ]. This gram-positive intracellular bacterium is widespread in the natural environment [ 5 ], and infections mostly arise following the consumption of contaminated food, such as unheated ready-to-eat meals and dairy products [ 6 7 8 ], because of the ability of L. monocytogenes to survive under salty or acidic conditions and grow at refrigeration temperatures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Listeriosis caused by Listeria monocytogenes is a bacterial infection with a high case-fatality rate (CFR) of approximately 20% to 30%; listeriosis occurs mainly in the elderly, neonates, immunocompromised patients, and pregnant women via central nervous system (CNS) infection and bloodstream infection (BSI) [ 1 2 3 4 ]. This gram-positive intracellular bacterium is widespread in the natural environment [ 5 ], and infections mostly arise following the consumption of contaminated food, such as unheated ready-to-eat meals and dairy products [ 6 7 8 ], because of the ability of L. monocytogenes to survive under salty or acidic conditions and grow at refrigeration temperatures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gawade et al (2010) also reported that L. monocytogenes can be confirmed by PCR using hlyA gene as a marker to differentiate L. monocytogenes from the other Listeria spp. In the present study, the PCR amplification of hlyA gene for the identification of L. monocytogenes used a set of primers as described by Park et al (2012) which yielded a product of 174 bp. The Type culture (MTCC 1143) and the isolates of L. monocytogenes from seafood contact surfaces swab yielded a similar product size of 174 bp on PCR amplification targeting hlyA gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ltd., Mumbai, India) according to the manufacturer's protocol and stored at -20°C until further use. Oligonucleotide primers for the PCR assay were selected based on the earlier published nucleotide sequence of hlyA gene (Ndahi et al 2013;Park et al 2012). Forward primer is 5 0 -GCATCTGCATTCAATAAAGA-3 0 and reverse primer is 5 0 -TGTCACTGCATCTCCGTGGT-3 0 with a product size of 174 bp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates' genetic similarity evaluation was performed with the RAPD technique (Random Amplification of Polymorphic DNA) (Park et al 2012). The reaction was performed using the OPA-11 primer with the 5'-CAATCGCCGT-3′ sequence (Ozbey et al 2006).…”
Section: Genetic Similarity Evaluation (Rapd-pcr)mentioning
confidence: 99%